HOUSE PRICE MOVEMENT FOR PRIMARY AND SECONDARY MARKETS: EVIDENCE FROM SELANGOR, MALAYSIA - Jalil, Haszlila; Mohd Tawil, Norngainy; Daud, Md Nasir; Ahmad, Aina Edayu (PLANNING MALAYSIA, 2018)
The aim of this study is to determine the trend of escalation for both primary and secondary housing units. This research applies the desk study approach which uses secondary data from statistical format, which is the property market report (PMR) from the year of 2004 to 2014. Data from the PMR was analysed by using descriptive statistics method which provides a general overview of the house price movement. The observation only focuses the house price movement from the (9) districts in Selangor state. Results show that even though the volume of transactions decreases, the prices of residential properties are steadily increasing which also indirectly escalates the secondary market price.